Epistemologi dan falsafah berkaitan terapi muzik dari perspektif cendekiawan Muslim - Roziah Sidik @ Mat Sidek; Azmul Fahimi Kamruzaman; Mohd Jailani Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2021)
This article studies the comparative analysis of epistemology and philosophy of music in the Islamic civilization according to the viewpoints of medieval scholars in the Islamic civilization. The scholars selected are al-Kindi, Ikhwan al-Safa, al-Farabi and Ibn Sina. The basis of this research begins from the polemic among scholars concerning the legal status of using music, whether permissible or forbidden, due to the absence of authenticated textual proof (nas qat’i) from al-Quran and protracted debate over the authenticity of hadith on the prohibition of music. Behind the debate is that music was applied as an Islamic psychotherapy method of treatment in hospitals of the medieval Islamic civilization such as Fez Hospital in Morocco, cAdudi Hospital in Baghdad, al-Mansuri Hospital in Cairo, Nuri Hospital in Damascus, al-Arghuni Hospital in Allepo, Gevher Nesibe Hospital and Giyaseddin Keyhusrev Medical Hospital in Kayseri, Keykavus Hospital in Sivas, Turan Malik Hospital in Divrighi, Pervane Bey Hospital in Tokat, Atabey Ferruh Hospital in Cankiri, Ali bin Pervane Hospital in Kastamonu, Amasya Hospital in Amasya, Fatih Hospital in Istanbul, Edirne Sultan Bayezid II Hospital in Edirne and Suleymaniye Hospital in Istanbul. This research uses qualitative methodology and library research method by analyzing various primary and secondary sources. Research results show that there is a slight discrepancy of views between supporters of neo-Pythagorean (al-Kindi and Ikhwan al-Safa) and Aristotelian (al-Farabi and Ibn Sina) schools of thought from the epistemological viewpoint. However, in terms of philosophy, there seems to be points of similarity in the matter of enhancement of moral and spiritual values for the sake of human well-being, whether physical or spiritual.